A case of clinical vampirism in Asia - Phang, Cheng Kar; Sekvakumar, Kayatri; Ang, Jin Kiat (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Clinical vampirism in psychiatric practice is very rare and usually associated with schizophrenia, antisocial personality disorder or paraphilia. An Asian case of clinical vampirism is described. It is about a 24-year-old Malay female, paramedic student, who craved for blood since childhood. She injured her sister and herself so that she could access and drink blood. There was no associated psychosis or medical problems. The craving for blood may represent her underlying craving for parental love and attention.